ECONOMIC GROWTH IN SHARIA BANKING TIME: PERTUMBUHAN WAKTU EKONOMI PERBANKAN SYARIAH - Zai, Niat Noverlin; samosir, Adelina Yessi Utama (UPMI Proceeding Series, 2023)
This study aims to analyze marketing strategies at PT. Proderma Sukses Mandiri, especially the marketing mix (Marketing Mix) applied by the company. Then to know the result of Strength, Weakness, Opportunities and Threat and strategy description so that it can be applied to increase product sales. Using SWOT, Matrix, EFAS, and IFAS research techniques and cartecius diagram. This research uses qualitative method, that is case study which produce descriptive data which poured in words. Data collection techniques in this study authors make direct visits to the PT. Proderma Sukses Mandiri to conduct a personal interview with President Director Mr. Sumarwoto and completed with sales data several years back. The conclusion of the analysis conducted on marketing strategy of PT. Proderma is a company that has run the marketing strategy correctly and precisely and at calculation of SWOT analysis which poured on cartesius proderma diagram is in position of quadrant 1 that is Growth. Which companies can develop, maintain and improve product quality so that people continue to believe in Proderma products. Then the company has fulfilled the character and paradigm of sharia marketing by winning mind share, market share and heart share. Although from the product variable side of its marketing mix, PT. Proderma is in charge of halal certificate from MUI. But in terms of its marketing process the company is honest with what is offered and not excessive.